Selenium alleviates toxicity in Amaranthus hypochondriacus by modulating the synthesis of thiol compounds and the subcellular distribution of cadmium. (March 2022) - Yang, Li; Li, Na; Kang, Yuchen; Liu, Jiaxin; Wang, Yuhao; Sun, Hui; Ao, Tianqi; Chen, Wenqing
Abstract: As a beneficial element, Selenium (Se) reduces toxic cadmium (Cd) absorption in many crops, but the effects of Se on Cd hyperaccumulator plants are unclear. This study examined the effects of Se on Amaranthus hypochondriacus (K472). The results showed that Se increased antioxidant enzyme activities, reduced Cd concentrations and toxicity, restored cell viability, and enhanced photosynthesis; these effects increased the biomass of roots, stems, and leaves by 59.87%, 53.85%, 44.19%, respectively, and these values exceeded the biomass of roots and stems in untreated control plants by 56.69% and 15.37%, respectively. Moreover, Se promoted PC synthesis, stably chelated Cd in the form of PC3 and PC4 and transported PC-Cd to vacuoles. Furthermore, Se protected organelles and reduced Cd migration by increasing Cd levels in cell walls and vacuoles. Interestingly, although the Cd content in K472 was decreased, Se maintained the total extracted Cd concentrations and its remediation efficiency by improving biomass and increased tolerance to Cd by approximately 5 times. The experimental results provide novel insights and methods for mitigating toxicity, promoting growth, and broadening the engineering application scope of K472; these results also provide a theoretical basis for further application of Se in soil with high Cd concentrations. Graphical abstract: Image 1 Highlights: Treat K472 with Se offers a new remediation strategy for high Cd pollution. Se increases the biomass of K472 by 1.5 times under Cd stress. Se protects organelles by increasing Cd contents in the cell wall and vacuole. Se inhibits Cd upward migration by chelating PC and isolates Cd in roots. Se-induced Cd detoxification results in excellent tolerance of K472 to high Cd levels.